Priya puts herself first - Fairbairn, Nathan; Msassyk (New York : Razorbill, 2023)
Priya Gupta and her friends Gabby Jordan and Mindy Park are the best dog-walkers in town and, although they each face challenges during the holidays, their friendship get them through it all.
Ages 3-7 years
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Graphic novels; Friendship -- Fiction; Dog walking -- Fiction; Dogs -- Fiction; Graphic novels